Electoral System and Public Spending - Perotti, Roberto (IMF Working Papers; Working Paper ;, 2001)
We study the effects of electoral institutions on the size and composition of public expenditure in OECD and Latin American countries. We present a model emphasizing the distinction between purchases of goods and services, which are easier to target geographically, and transfers, which are easier to target across social groups. Voters have an incentive to elect representatives more prone to transfer spending in proportional systems. The model also predicts higher primary spending in proportional systems when the share of transfer spending is high. After defining rigorous measures of proportionality, we find considerable empirical support for our predictions.